Formation of Neologisms in Modern English and Their Social Causes - Navbaxor Karshiboyeva (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article is dedicated to the analysis of the formation of neologisms in modern English and the social reasons that prompted their emergence. The research shows that the emergence of new words is directly linked to extralinguistic factors (non-linguistic factors) such as technological revolutions, political changes, cultural trends, and the need for inclusivity in society. Through corpus analysis and a sociolinguistic approach, the mechanisms by which neologisms enter the vocabulary are studied, concluding that they are an important indicator reflecting the adaptability of the language.